FINGER BRUSH, AN ALTERNATIVE FOR REMOVING PLAQUE IN CHILDREN UNDER FIVE YEARS OLD - Burhanudin Pasiga (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of the present study was to test the effectiveness of a finger brush in removing plaque compared with that of a regular toothbrush. For this study, 30 subjects were selected and divided into 2 groups. Fifteen subjects received a finger brush; another group of subjects received a regular toothbrush. The amount of dental plaque was scored by the modified PHP method. Plaque scored was carried out at five areas per tooth. The results showed that the overall reduction in plaque was 67,25% for the regular toothbrush and 44,93% for the finger brush; it was a non significant differenct (p>0,170). The plaque removing efficacy of the finger brush was poorest at the mesial area (28,1% plaque reduction) compared with that of the regular toothbrush (68,8% plaque reduction). It was concluded that the plaque by means of finger brush could be an acceptable alternative to the use for children under five years of age.